Locally Advanced Pancreatic Cancer. Looking Beyond Traditional Chemotherapy and Radiation - Savir, Guy; Huber, Kathryn E; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
About a third of all pancreatic cancer is found to be locally advanced at the time of diagnosis, where the tumor is inoperable but remains localized to the pancreas and regional lymphatics. Sadly, this remains a universally deadly disease with progression to distant disease being the predominant mode of failure and average survival under one year. Optimal treatment of these patients continues to be an area of controversy, with chemotherapy alone being the treatment preference in Europe, and chemotherapy followed by chemoradiation in selected patients, preferred in the USA. The aim of this paper is to summarize the key abstracts presented at the 2013 ASCO Annual Meeting that address evolving approaches to the management of locally advanced pancreatic cancer. The late breaking abstract (#LBA4003) provided additional European data showing non-superiority of chemoradiation compared to chemotherapy in locally advanced pancreatic cancer patients without distant progression following 4 months of chemotherapy. Another late breaking abstract, (#LBA4004), unfortunately showed a promising new complement to gemcitabine and capecitabine using immunotherapy in the form of a T-helper vaccine did not translate to improved survival in the phase III setting. Image: Tufts University Medford/Somerville campus. Medford, MA, USA.